Pengaruh Influencer Marketing dan Brand Image terhadap Keputusan Pembelian Produk Skintific di Bekasi - Rizalsjah, Viona Salsabilah; Sulistyowati, Ari (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the influence of influencer marketing and brand image on purchasing decisions for skincare products, despite the significant impact of this phenomenon on marketing strategies within the beauty industry. The aim of this research is to analyze the effect of influencer marketing and brand image on purchasing decisions for Skintific products in the Bekasi area. A quantitative method with a survey approach was employed, using purposive sampling of 115 respondents residing in Bekasi who had previously purchased Skintific products. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of SPSS version 25. The results indicate that both influencer marketing and brand image have a positive and significant effect on purchasing decisions, both partially and simultaneously, with brand image exerting the most dominant influence. These findings reinforce the theory that brand perception and social media-based communication strategies play a strategic role in shaping consumer behavior in the digital era. The study provides theoretical contributions to the literature on digital marketing and practical recommendations for businesses to optimize promotional strategies through influencer collaboration and brand image enhancement. It also opens opportunities for further exploration by expanding variables and research areas to gain deeper insights.